Novel Risk Scoring System for Patients with Metastatic Renal Cell Carcinoma Treated with Immune Checkpoint Inhibitors. (5th December 2019) - Martini, Dylan J.; Liu, Yuan; Shabto, Julie M.; Carthon, Bradley C.; Hitron, Emilie Elise; Russler, Greta Anne; Caulfield, Sarah; Kissick, Haydn T.; Harris, Wayne B.; Kucuk, Omer; Master, Viraj A.; Bilen, Mehmet Asim
Abstract: Background: The International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) criteria are the gold standard for risk‐stratifying patients with metastatic renal cell cancer (mRCC). We developed a novel risk scoring system for patients with mRCC treated with immune checkpoint inhibitors (ICIs). Methods: We performed a retrospective analysis of 100 ICI‐treated patients with mRCC at Winship Cancer Institute from 2015 to 2018. Several baseline variables were collected, including markers of inflammation, body mass index (BMI), and sites of metastatic disease, and all were considered for inclusion in our risk scoring system. Upon variable selection in multivariable model, monocyte‐to‐lymphocyte ratio (MLR), BMI, and number and sites of metastases at baseline were used for risk score calculation. Patients were categorized using four‐level risk groups as good (risk score = 0), intermediate (risk score = 1), poor (risk score = 2), or very poor (risk score = 3–4). Cox's proportional hazard model and the Kaplan‐Meier method were implemented for survival outcomes. Results: Most patients were male (66%) with clear cell renal cell carcinoma (72%). The majority (71%) received anti–programmed cell death protein‐1 monotherapy. Our risk scoring criteria had higher Uno's concordance statistics than IMDC in predicting overall survival (OS; 0.71 vs. 0.57) and progression‐free survival (0.61 vs. 0.58). Setting good risk (MLR <0.93, BMI ≥24, and D_Met = 0) as the reference, the OS hazard ratios were 29.5 (95% confidence interval [CI], 3.64–238.9), 6.58 (95% CI, 0.84–51.68), and 3.75 (95% CI, 0.49–28.57) for very poor, poor, and intermediate risk groups, respectively. Conclusion: Risk scoring using MLR, BMI, and number and sites of metastases may be an effective way to predict survival in patients with mRCC receiving ICI. These results should be validated in a larger, prospective study. Abstract : Considering the increasing number of treatment options for patients with metastatic renal cell carcinoma, it is becoming more important to identify factors that increase the likelihood of responses to systemic therapy. This article describes a novel risk scoring system for patients with metastatic renal cell carcinoma treated with ICI, focusing on risk from systemic inflammation, number and sites of metastatic disease, and body composition.